2019
DOI: 10.1002/cam4.2218
|View full text |Cite
|
Sign up to set email alerts
|

The propensity of invasive circulating tumor cells (iCTCs) in metastatic progression and therapeutic responsiveness

Abstract: Circulating tumor cells (CTCs) are important clinical indicators of metastatic progression and treatment efficacy. However, because of their low number and heterogeneity, reliable patient‐derived CTC models are not readily available. We report here the isolation and characterization of the invasive population of CTCs, iCTCs, from blood of 10 patients with epithelial ovarian cancer (EOC) and one pancreatic cancer patient based on the avidity of tumor cells toward an artificial collagen‐based adhesion matrix (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…During the last 20 years, CTCs have become an stronger marker for prognosis and response to the treatment 39,40 . CTCs are implicated in disease dissemination and they have been proposed as indicators of minimal residual disease 41 , which cannot be detected by standard imaging methodologies in the clinical practice 42,43 . miRNAs profiles have been related to the metastatic spread of the tumour, characterized by the presence of CTCs 44 .…”
Section: Discussionmentioning
confidence: 99%
“…During the last 20 years, CTCs have become an stronger marker for prognosis and response to the treatment 39,40 . CTCs are implicated in disease dissemination and they have been proposed as indicators of minimal residual disease 41 , which cannot be detected by standard imaging methodologies in the clinical practice 42,43 . miRNAs profiles have been related to the metastatic spread of the tumour, characterized by the presence of CTCs 44 .…”
Section: Discussionmentioning
confidence: 99%
“…CAM invasion assay kits are sold under the Vita assay TM brand (Applied DNA Sciences, Stony Brook, NY, USA). These kits include 6-well plates in which the bottom of each well is coated with a CAM layer that may be fluorescently labeled [ 22 , 58 ]. The methods mentioned in this section are summarized in Table 1 .…”
Section: Current Enrichment and Detection Techniquesmentioning
confidence: 99%
“…Circulating tumor cells (CTCs) refer to a population of cells that have detached from the tumor and are circulating in the peripheral blood and/or lymphatic system. They are found in almost all solid malignant tumors and play a crucial role in the metastatic process [ 5 , 6 , 7 ]. Furthermore, recent studies have indicated that tumor cells can disseminate even in the early stages of tumor progression [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%